1992
DOI: 10.1164/ajrccm/145.1.130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cardiac Output on Oxygen Exchange in Acute Pulmonary Embolism

Abstract: We investigated interactions between cardiac output, VA/Q distribution pattern, pulmonary gas exchange, O2 transport, and tissue oxygenation in 16 patients during the acute phase of pulmonary embolism (PE). The effects of breathing room air, O2 therapy (FIO2 = 0.40) (11 patients), and dobutamine (four patients) were studied after right catheterization using the multiple inert gas elimination technique. The pattern of VA/Q ratio distributions was found to depend essentially on cardiac output level. The individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 2 publications
4
39
1
4
Order By: Relevance
“…The pattern of distribution of either ventilation or perfusion, however, depends largely on cardiac output. (13) When such patients continue to have normal cardiac output, blood flow redistribution can result in the formation of areas of low ventilation or perfusion within the lung zone unaffected by thromboembolism. This means that there is an overperfusion of non-embolised regions, which in turn leads to hypoxaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of distribution of either ventilation or perfusion, however, depends largely on cardiac output. (13) When such patients continue to have normal cardiac output, blood flow redistribution can result in the formation of areas of low ventilation or perfusion within the lung zone unaffected by thromboembolism. This means that there is an overperfusion of non-embolised regions, which in turn leads to hypoxaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The factor observed to play an extremely important role in hypoxaemia in patients with APE is reduced mixed venous oxygen tension, which is a direct consequence of low cardiac output. (13,14) Although decreased cardiac output plays an important role in hypoxaemia, hypoxaemia can occur regardless of changes in cardiac output. Indeed, patients with massive pulmonary embolisms can present with severe hypoxaemia even if their cardiac output and blood pressure are normal.…”
Section: Discussionmentioning
confidence: 99%
“…Jardin et al 1979). Several previous investigators, who pioneered in this area using the MIGET method, found inconsistent relationship between arterial oxygenation and cardiac output but did not have a more detailed explanation (Manier et al 1992). In the present study, we specifi cally studied the mechanisms on how regional pulmonary blood fl ow was distributed inside the embolized lung when the cardiac output was intermittently altered, in an attempt to elucidate the underlying pathophysiology.…”
Section: Discussionmentioning
confidence: 93%
“…25,35,98 Some suggested that this inverse correlation was due to the abolition of hypoxic pulmonary vasoconstriction due to the concomitant higher PvO 2 . 99 As it turns out, the answer lies mostly in the heterogeneity of regional blood flow.…”
Section: Why Does Hypoxemia Worsen When Qt Is Increased?mentioning
confidence: 99%